The Role of Globalization as an Ideology in Aggravating Violence in V.S. Naipaul’s A House for Mr Biswas (1961) - Hadjadj, Hadjer; Nouioua ,Wafa (University of Ammar Theledji -Laghouat, 2020)
This dissertation provides a Marxist reading of A House for Mr Biswas (1961), a masterpiece written by the Indo-Trinidadian writer V.S Naipaul, in terms of Louis Althusser’s Ideology, Ideological State Apparatuses, and interpellation’. Althusser developed the notion of interellation’ tat is te system through which individuals become subjects by what he called Ideological State Apparatuses. These latter, being the foundations through which the dominant power imposes its control over the masses, are highly prominent in the novel and are founded by foreign forces. This work then, aims to investigate the possibility that globalization may operate as an ideology, and to test how does globalization as an ideology aggravate both domestic and social violence in the case studied. This dissertation also represents a closer examination of the impact of globalization as an ideology on the postcolonial countries. The issues brought by globalization as an ideology to the Caribbean island of Trinidad and Tobago being a country that experienced colonialism are present in this work. The exploratory, descriptive, and analytical method is used then, as an attempt to bridge the gap between concepts like globalization, ideology, and violence